Advancement, opportunities, and practices in telehealth technology - Kumar, S.N. 1985-; Zafar, Sherin (Advances in medical technologies and clinical practice (AMTCP) book series, 2022)
"This book provides exposure in Digital Health Technology and Telemedicine domains such as Intelligent computing technologies, 5G Wireless Communications, Smart appliances, and autonomous transportation to assist in the discovery of solutions for the key challenges faced by Digital Health Technology entrepreneurs and enterprises across the world through sharing of research ideas"